Performance of a Vertical‐Slot Fish Pass for the Sea Lamprey Petromyzon marinus L. and Habitat Recolonization. (8th July 2016) - Pereira, E.; Quintella, B. R.; Mateus, C. S.; Alexandre, C. M.; Belo, A. F.; Telhado, A.; Quadrado, M. F.; Almeida, P. R.
Abstract: In 2011, a vertical‐slot fish pass was built at the Coimbra Açude‐Ponte dam (Mondego River, Portugal), approximately 45 km upstream from the river mouth. The performance of this infrastructure for sea lamprey passage was evaluated between 2011 and 2015 using several complementary methodologies, namely radio telemetry [conventional and electromyogram (EMG)], passive integrated transponder (PIT) telemetry and electrofishing surveys. During the study period, the electrofishing revealed a 29‐fold increase in the abundance of larval sea lamprey upstream of the fish pass. Of the 20 radio‐tagged individuals released downstream from the dam, 33% managed to find and successfully surpass the obstacle in less than 2 weeks, reaching the spawning areas located in the upstream stretch of the main river and in one important tributary. Fish pass efficiency was assessed with a PIT antenna installed in the last upstream pool and revealed a 31% efficiency, with differences between and within migratory seasons. Time of day and river flow significantly influenced the attraction efficiency of the fish pass, with lampreys negotiating it mainly during the night period and when discharge was below 50 m 3 s −1 . Sea lampreys tagged with EMG transmitters took 3 h to negotiate the fish pass, during which high muscular effort was only registered during passage, or passage attempts, of the vertical slots. The use of complementary methodologies provided a comprehensive passage evaluation for sea lamprey, a species for which there is a considerable paucity of valuable data concerning behavioural, physiological and environmental influences on obstacle negotiation. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.